The epidemiology of patellar luxation in dogs attending primary-care veterinary practices in England - O’Neill, Dan G. (Canine Genet Epidemiol, 2016)
BACKGROUND: Canine patellar luxation is one of the most common orthopaedic disorders of dogs and is a potential welfare concern because it can lead to lameness, osteoarthritis and pain. However, there are limited epidemiological data on the disorder relating to the general population of dogs in England. This study aimed to investigate the VetCompass Programme database of dogs attending primary-care veterinary practices in England to report on the prevalence, risk factors and clinical management of diagnosed patellar luxation cases. RESULTS: The study included all dogs with at least one electronic patient record in the VetCompass database from September 1(st), 2009 to August 31(st), 2014. Candidate patellar luxation cases were identified using free-text word searching of the clinical notes and VeNom diagnosis term fields. Univariable and multivariable binary logistic regression modelling was used for risk factor analysis. The overall dataset comprised 210,824 dogs attending 119 clinics in England. The prevalence of patellar luxation diagnosis in dogs was 1.30 % (95 % confidence interval (CI) 1.21–1.39). Of the 751 incident cases, 293 (39.0 %) received medical management, 99 (13.2 %) received surgical intervention and 28 (3.7 %) were referred for further management. Multivariable modelling documented 11 breeds with increased odds of patellar luxation compared with crossbred dogs, including the Pomeranian (odds ratio [OR]: 6.5, 95 % CI 4.0–10.7, P < 0.001), Chihuahua (OR: 5.9, 95 % CI 4.4–7.9, P < 0.001), Yorkshire Terrier (OR: 5.5, 95 % CI 4.3–7.1, P < 0.001) and French Bulldog (OR: 5.4, 95 % CI 3.1–9.3, P < 0.001). Dogs with bodyweight below their mean for breed and sex had a 1.4 times odds of diagnosis (95 % CI 1.2–1.6, P < 0.001). Dogs aged ≥ 12.0 years showed 0.4 times the odds (95 % CI 0.3–0.5, P < 0.001) compared with dogs aged < 3.0 years. Females had 1.3 times the odds (95 % CI 1.1–1.5, P < 0.001), neutered dogs had 2.4 times the odds (95 % CI 1.8–3.2, P < 0.001) and insured dogs had 1.9 times the odds (95 % CI 1.6–2.3, P < 0.001). CONCLUSIONS: Patellar luxation warrants inclusion as a welfare priority in dogs and control strategies that include this disorder should be considered as worthwhile breeding goals, especially in predisposed breeds.